THE FUNDAMENTALS OF SYSTEMS APPROACH IN ENSURING THE HYDROLOGICAL SAFETY «ACTIVITIES» IN THE NTS «ENVIRONMENT - OBJECT OF ACTIVITY - POPULATION» - Elena Anatolevna Semyonova; Alexey Vyacheslavovich Aliferov (Современная наука и инновации, 2022)
Goal is to ensure the hydrological safety of hydraulic structures for storage, diversion, and other types of hydraulic systems associated with water resources use and protection of territories from flooding and underflooding in the considered spatial limits of basin geosystems in the range of formation of river runoff: surface and underground.